Generative Agent Swarm: Bacterial Foraging with LLM-Mediated Pheromone Communication - Daniel A. Ferreira1 (Metaheuristic Algorithms with Applications, 2026)
This paper introduces GAS-BFO, a novel metaheuristic optimization algorithm designed to address surrogate-assisted expensive black-box optimization. The proposed approach leverages Bacterial Foraging + LLM pheromone + collective memory to achieve robust and efficient performance across diverse problem instances. Unlike existing methods that rely on fixed search operators and static parameter configurations, GAS-BFO incorporates adaptive mechanisms that dynamically adjust the search strategy based on real-time landscape analysis. We provide a rigorous theoretical framework establishing convergence guarantees under mild assumptions, along with a detailed complexity analysis demonstrating the algorithm's computational efficiency. The experimental evaluation employs evaluate under distributional shift: train distribution → test distribution with controlled divergence, featuring domain shift resilience quantification. Statistical significance is assessed using Kruskal-Wallis + Dunn's, Cliff's delta, with effect size reporting to quantify practical significance. Results demonstrate that GAS-BFO achieves statistically significant improvements over nine state-of-the-art baselines, with an average performance gain of 22.5% and large effect sizes (Cohen's d > 0.8). Ablation studies confirm the contribution of each algorithmic component, and sensitivity analysis identifies the most influential parameters. The framework is validated on real-world problem instances, demonstrating practical applicability and robustness under varying conditions.